The effects of price information and communication in markets with capacity constraints: an experiment - Momsen, Katharina (Journal of economics & management strategy, 2021)
Limited price information and miscoordination reduce buyer surplus in markets with capacity-constrained sellers. In an experiment, I study the effects of facilitating buyer coordination through communication and increasing the availability of price information. Improved coordination leads to an increase in trade and, under full price information, in prices. Whereas sellers benefit, buyers suffer more from the increase in prices than they benefit from the increase in trade. The impact of better price information depends on the presence of communication: with communication, an additional informed buyer induces sellers to raise their prices, yet without communication, one additional informed buyer provokes a price decrease.
Gesehen am 07.08.2023